The Role of Employee Characteristics and Quality of Work Life in Improving Performance at Mother and Children Glamour Husada Kebun Hospital, Bangkalan, Indonesia - Setya Haksama; Ditami Rahmarista; M. Farid Dimjati Lusno; Diansanto Prayoga; Shyamkumar Sriram; Arga Setyo Adji; Syahprevi Rayyan Zeinsar; Syadza Zahrah Shedyta (Health Dynamics, 2025)
Background: Human resource management plays a vital role in achieving hospital goals, including improving service quality by optimizing human resource talent efficiently. The quality of work significantly affects employee performance. Employees who experience a supportive and conducive work environment are more motivated, engaged, and likely to provide optimal results, contributing to organizational success. This study aims to analyze the influence of employee characteristics and quality of work life on employee performance at RSIA Glamour Husada Kebun Bangkalan. Methods: A quantitative research method with a cross-sectional approach was employed. The study involved all employees of RSIA Glamour Husada Kebun Bangkalan, with a sample of 74 respondents selected through total sampling. Data were collected via questionnaires covering employee characteristics, quality of work life, and employee performance. Binary logistic regression was used for data analysis. Results: Employee characteristics (p = 0.265) did not have a significant influence on performance simultaneously. However, the quality of work life (p = 0.000) significantly influenced performance simultaneously. Among the employee characteristics, the length of service (p = 0.008) had a significant effect on performance. All dimensions of quality of work life were proven to partially affect employee performance. Conclusion: Employee performance is significantly influenced by the length of service and various dimensions of quality of work life. These findings highlight the importance of fostering a supportive work environment and recognizing the critical role of tenure in enhancing the performance of hospital employees.